Budaya Panjang Mulud Sebagai Daya Tarik Wisata Perkotaan Berbasis Masyarakat di Kota Serang - Sahabudin, Arfah; Tahir, Rusdin; Hadian, M. Sapari Dwi; Nugraha, Awaludin (Journal of Indonesian History, 2019)
Panjang Mulud culture is a tradition in the City of Serang. Panjang Mulud was performed in commemoration of the birthday of the Prophet Muhammad. which is also called Maulidan. The purpose of this study is to reveal how Panjang Mulud culture as a community-based urban tourism attraction in the City of Serang. The research method used is a qualitative method. Primary data collection is done by observation and in-depth interview techniques. In addition, a literature study was also carried out. The data analysis technique uses an interactive model. Consists of three activities, namely (1) condensing data; (2) presenting data; (3) drawing conclusions and verification. The results showed that the Panjang Mulud Tradition had become an attraction for cultural tourism in the City of Serang. Panjang Mulud is part of community-based urban tourism attractions. The Long Mulud tradition is still a local event which has not been able to attract wider tourists. While Panjang Mulud can be more interesting if it is served through a more integrated and interesting cultural event that is through a Panjang Mulud Festival. As one way to preserve culture, religion, social and mutual cooperation, the City Government of Serang has supported Panjang Mulud in the form of annual activities in the form of the Long Mulud parade with all OPDs to the Serang City square. Keywords: Panjang Mulud, Urban Tourism, Tradition, Festival, Community Empowerment